Socioemotional Linguistic and Rhetorical Markers of the September 2024 Hostilities in Lebanon: Insights from Academics across Lebanese Universities - Joudi, Nadine Sami; Ayoub, Nawal Nabih; Arnous, Hanan Nadim (European Scientific Journal, ESJ, 2025)
Several theoretical frameworks examine the intricate relationship between language and socioemotional dynamics. Drawing upon Fairclough’s tripartite framework of critical discourse analysis, this research case study endeavors to show how linguistic expression encapsulates the socioemotional experiences of displacement, trauma, resilience, and solidarity among university faculty impacted by the airstrikes in Lebanon in 2024. This research’s main objective is to scrutinize the use of lexical choices and rhetorical strategies to articulate these emotions while reflecting social and ideological constructs in reaction to the prevailing hostilities. Data were collected from the perspectives of sixty-two instructors and staff members across thirteen Lebanese universities through a twenty-item online survey, which served as the foundation for both statistical and descriptive analysis. Furthermore, as a result, twenty-six online narrative reflection logs provided a linguistically nuanced representation of socioemotional linguistic indicators related to displacement, trauma, resilience, and solidarity, while also invoking rhetorical techniques such as similes, metaphors, hypophoras, epizeuxis, and anaphoras that signified a connection to a collective identity.